Responding to the Covid-19 in residential long-term care in Poland: what has been done to increase safety of the elderly - Sowa-Kofta, Agnieszka (Ревија за социјална политика/Journal of Social Policy, 2020)
The outbreak of Covid-19 put a pressure on long-term care from the first weeks of the pandemic. As in most of European countries, United States and Canada particularly residential care facilities were in danger of an outbreak and its negative consequences, including deaths of cared for. The pandemic immediately and painfully depicted weaknesses of the long-term care system. The article presents information on the Covid-19 epidemic in Poland and discusses methods adopted to respond to the outbreak in residential long-term care in the first months of the pandemic.